Studies on the Population Dynamics of Shot-hole Borer Scolytus nitidus Schedl (Coleoptera: Scolytidae) - Buhroo, A. A.; Chishti, M. Z.; Masoodi, M. Amin (Indian Forester, 2004)
Studies on the seasonal population trends of Scolytus nitidus on apple trees indicated adult emergence from middle of April to middle of October with two marked peaks of swarming in April-May and in July. The adults generally appeared on wing during the day time. The emergence was maximum in the second fortnight of July. There was also a third partial generation but the third time swarming was not clearly demarcated in nature mainly due to the fact that all the individuals of second brood could not complete their development and the second swarming beetles emerged for a prolonged period overlapping with the third time emergence. The emergence period for one brood lasted for 87 days. The peaks of beetle populations were found to be correlated with higher temperatures. The emergence started at a monthly maximum mean temperature of 22.5Â°C and minimum mean temperature of 8.3Â°C around the middle of April.